THE INFLUENCE OF PERSUASIVE COMMUNICATION OF TIKTOK SHOP LIVE SHOPPING BRAND AMBASSADOR GLAD2GLOW ON BUYING INTEREST - Oktavia Sri Wahyuni; Danang Trijayanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The purpose of this study is to analyze how consumers' interest in buying Glad2Glow skincare products is influenced by brand ambassadors and persuasive communication strategies used in TikTok live shopping. This study uses a quantitative methodology by surveying 100 active TikTok users in Papanggo Village, North Jakarta, aged 17 to 34 years. Each item in the research instrument is valid and reliable, according to the results of the validity and reliability test. Persuasive communication strategies, brand ambassadors and buying interest are strongly and significantly correlated, according to Pearson's correlation research. Both independent factors significantly influence buying interest, according to multiple linear regression analysis, with persuasive communication strategies having the greatest influence.